PERLINDUNGAN HUKUM TERHADAP PEMEGANG SAHAM MINORITAS PADA PERUSAHAAN YANG MELAKUKAN AKUISISI - Ruth Marbun; Bismar Nasution; Mahmul Siregar (TRANSPARENCY, 2016)
ABSTRACT LEGAL PROTECTION FOR MINORITY SHAREHOLDERS ON COMPANIES THAT MAKE ACQUISITIONS The development of the current economic system encourages a lot of companies to make acquisitions in order to strengthen their organization's condition. The acquisition that happens often cause unfairness to minority shareholders. However, based on Law Number 40 of 2007 on Limited Liability Company, it explains that the acquisition must show mutual benefit for both parties. Therefore there is a need to form some type of protection for the minority shareholders in the implementation of the acquisition